Age differences in the temporal stability of a male African elephant (Loxodonta africana) social network. (27th September 2019) - Murphy, Derek; Mumby, Hannah S; Henley, Michelle D
Abstract: Social animals live in complex and variable socio-ecological environments where individuals adapt their behavior to local conditions. Recently, there have been calls for studies of animal social networks to take account of temporal dynamics in social relationships as these have implications for the spread of information and disease, group cohesion, and the drivers of sociality, and there is evidence that maintaining stable social relationships has fitness benefits. It has recently been recognized that male elephants form strong social bonds with other males. The nature of these relationships, and thus network structure, may vary over time in response to varying environmental conditions and as individuals age. Using social network analysis, we examine the stability of relationships and network centrality in a population of male African elephants. Our results suggest that males may maintain stable social relationships with others over time. Older males show greater stability in network centrality than younger males, suggesting younger males face uncertainty in transitioning to adult society. For elephants, where older individuals function as social repositories of knowledge, maintaining a social network underpinned by older males could be of particular importance. Lay Summary: Male elephants leave the herd they were born into when they reach adolescence. They then face the challenge of adapting to a new social environment—adult male society. Using social network analysis, we show that older males are more stable in their social behavioral strategies over time than younger males. Older males, like older females, may act as social "mentors" for younger individuals and may be of particular importance for maintaining group cohesion, and thus for conservation efforts.